Effect of radio frequency dielectric heating on functionality of nonfat dry milk - Wang, Lu (Kansas State University, 2016)
Radio frequency dielectric heating (RFDH) can provide rapid and uniform heating throughout the products' mass, and can be used to bake, dry, and defrost foods. Studies have shown that when RFDH induced a 5-log reduction of Salmonella spp. in nonfat dry milk (NDM), whey protein nitrogen index (WPNI) decreased, suggesting that functional properties of the NDM might be impacted. This research was conducted to determine if RFDH affected the functional properties of NDM [high-heat (HH) and low-heat (LH)]. Nonfat dry milk were treated to 75, 80 and 85°C in the RFDH unit, then were held for 125, 63 and 43 min for LH-NDM or 115, 52 and 43 min for HH-NDM, and cooled to ~23 ± 1°C. Powders were evaluated for WPNI , nitrogen solubility index, and color. Maillard browning and functional properties of NDM samples were evaluated after NDM was rehydrated to 3.5% protein with deionized water, and adjusted to pH 7.00. Glucono-delta-lactone was added in rehydrated NDM (3.5% protein; natural pH) as an acidifying agent to form milk gels, and the physical properties of the gels were determined. Two replications were conducted and data were analyzed with two-way ANOVA (RFDH and NDM) and Tukey mean differentiations (p ≤ 0.05). Results showed that LH-NDM (collapsed for RFDH treatments) had 5.7% less viscosity, 20.9% less overrun, 27.4% less foam stability, as well as 15% less water holding capacity compared with HH-NDM (collapsed for RFDH treatments). This can be explained by the natural whey protein denaturation differences in the HH-NDM and LH-NDM. Viscosity and surface tension were impacted by the RFDH treatment. NDM (HH and LH) treated to 85°C had 10% greater viscosity than the control, and the NDM treated to 75°C had less surface tension compared with samples treated to 80°C, 85°C and the control. Overall, RFDH decreased WPNI in LH-NDM, but not HH-NDM. The SDS-PAGE gel images provided supportive evidence to the WPNI results. RFDH is a processing technology that could change a few functional properties of NDM in this study, which makes it a promising method that may be further exploited for various food applications, such as emulsifiers, foaming agents, etc. However, potential negative impacts, such as color change caused by Maillard reaction, loss of WPNI in LH-NDM, cannot be neglected.
Keywords: Radio frequency dielectric heating; Nonfat dry milk; Functionality